THEA-CODE: a design tool for the conceptual design of hybrid-electric aircraft with conventional or unconventional airframe configurations - Palaia, Giuseppe; Zanetti, Davide; Abu Salem, Karim; Cipolla, Vittorio; Binante, Vincenzo (Mechanics & industry : an international journal on mechanical sciences and engineering applications, 2021)
The aviation world is dealing with the development of new and greener aviation. The need for reducing greenhouse gas emission as well as the noise is a critical requirement for the aviation of the future. The aviation world is struggling with it, and a compelling alternative can be the electric propulsion. This work aims to present THEA-CODE, a tool for the conceptual design of hybrid-electric aircraft. The tool evaluates the potential benefits of the electric propulsion in terms of fuel burnt and direct and indirect CO 2 emissions. THEA-CODE is suitable not only for conventional “wing-tube” configurations but also for unconventional ones, such as the box-wing. The results show a significant reduction of fuel burnt adopting batteries with energy density higher than the current state of the art. A procedure to find the potential best compromise configurations is presented as well.